Service design for innovation in small and medium businesses - Carvalho Proenca, Joaquin (2019)
An innovation program designed and implemented with two Peruvian small, medium business in health and hotel industries focused on value creation goal while developing products and services innovation. For insights, ideas generation, solutions validation and prototyping proposals at the front-end open innovation strategy were used both indirect and direct methods; trends research, customer journey mapping, ethnography, interaction with users with depth interviews and dynamic group sessions. The research sought both to test the program and deploy the methods developed in business to advance capabilities for knowledge management and iterative processes. As a result small and medium businesses can develop Services Design according to their human and financial limitations using processes based on four axes; scanning the environment immersion learning, gamification, Lean and Design Thinking. The research concluded there are alternative paths that take into account and involve greater collaboration of users that businesses can explore and exploit. Innovation processes do not have to be long, uncertain or expensive for small and medium businesses.